Paediatric Langerhans cell histiocytosis with diabetes insipidus: remarkable recovery journey - Rai, Versha Rani; Zulqarnain Buriro; Roshia Parveen; Mohsina Noor; Heeranand Rathore (Journal of the Pakistan Medical Association, 2024)
A rare condition known as Langerhans cell histiocytosis (LCH) is characterised by the clonal growth of dendritic cells called Langerhans cells, which play a significant role in the immune system. A diverse range of clinical presentations are probable as a result of this condition's ability to develop in different systems of the body. LCH presents with variable clinical manifestations, demonstrated by a range from specific multisystem involvement to more extensive bone abnormalities. This case report details the clinical course of a four-year-old male who presented with rash on the scalp and multiple lumps on the head for the past three months and a history of polyuria for two months. The findings were indicative of Langerhans cell histiocytosis after clinical and histological investigative studies. Moreover, endocrinological investigations demonstrated the development of central diabetes insipidus, as a complication. Keywords: Langerhans cell histiocytosis, Central diabetes insipidus, Polyuria, Multidisciplinary care, Chemotherapy.